2016
DOI: 10.21630/maa.2016.67.08
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of food residues and cooking practices in the Medieval Hospital of Santa Maria della Scala in Siena (Central Italy)

Abstract: El artículo trata sobre el estudio del uso de algunas cerámicas medievales y de los alimentos preparados y consumidos en el Hospital medieval del Santa Maria della Scala en Siena (Italia Central). Esta investigación muestra la integración entre los datos obtenidos con el análisis arqueológico y arqueométrico (utilizando el análisis de residuos orgánicos) de las cerámicas y la investigación sobre los documentos históricos encontrados en el mismo contexto, el hospital medieval del Santa Maria della Scala en Sien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The presence of methyl dehydroabietic acid indicates that the resin has been heated with wood, likely through the production of pitch or tar [ 101 , 102 ]. Pitch or pine tar may have been stored and prepared in the cooking pots for use as a sealant, adhesive or to waterproof boats as observed in other medieval contexts [ 89 , 90 , 103 ]. There are also accounts of dipping the stem of fruits in pitch (grapes and pears) to preserve them [ 42 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of methyl dehydroabietic acid indicates that the resin has been heated with wood, likely through the production of pitch or tar [ 101 , 102 ]. Pitch or pine tar may have been stored and prepared in the cooking pots for use as a sealant, adhesive or to waterproof boats as observed in other medieval contexts [ 89 , 90 , 103 ]. There are also accounts of dipping the stem of fruits in pitch (grapes and pears) to preserve them [ 42 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, analytical procedures for the identification of small organic acids provided crucial evidence that fruits were incorporated in everyday culinary practices. A multifaceted analytical approach, including the identification of fruit products in domestic containers, has had its beginning in small corpus analysis of medieval ceramics [89,90,103,114]. This research has for the first time applied these methods systematically to a large corpus of samples.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Islamic cooking pots and other domestic containers from 9th-12th century contexts in Sicily has shown that a wide range of animal products, fruits and vegetables were processed, and has yielded important insight into the use of resources in both urban and rural contexts under the same regimes [2]. Previously, residue analysis has been undertaken on pottery from Italian 12th-13th century contexts [3][4][5][6][7], and this approach has also been used to examine the impact of the Norman conquest of England on culinary habits, with particular focus on lesser represented rural populations [8]. However, to date, no study has assessed the use of pottery vessels in post-Islamic contexts in Sicily.…”
Section: Introductionmentioning
confidence: 99%